Impact of changing location and power of a PV system in electrical distribution networks, integrating MATLAB and OpenDSS (2018)
This paper presents the electrical impact of connecting a photovoltaic (PV) system without storage to the electric distribution network 13-bus IEEE test case, integrating MATLAB and OpenDSS using a fluctuated vector of irradiance as an input for the PV system. The capacity of the primary source is reduced to a value where the system requires to add PV modules to provide a reliable source of power. PV modules are placed in both source bus and buses affected by voltage drops. Then, PV source is progressively increased to evaluate the voltage variations when combining PV and conventional sources. The results showed how a reduction in the generation affects the voltage levels of the system and how the inclusion of PV modules located in specific nodes tend to recover the system.